Using d/dt (e^t) = e^t and d/dt (tan t) = sec^2 t

`y' = d/dt (tan e^t) + d/dt e^(tan t)`

`= sec^2 (e^t) d/dt e^t + e^(tan t) d/dt (tan t)`

`= e^t sec^2(e^t) + e^(tan t) sec^2 t`

hope this helps.

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now